Analisis Yuridis Pembatalan Sertifikat Hak Milik No. 212/Pasar Pangururan yang Diterbitkan oleh Kantor Pertanahan Kabupaten Samosir Ditinjau Berdasarkan Putusan Pengadilan Tata Usaha Negara Medan No. 35/g/2020/Ptun-Mdn yang Telah Berkekuatan Hukum Tetap (Inkrach Van Gewijsde) - Refi Rafika Chairunnisa; Muhammad Yamin; Rosnidar Sembiring (Jurnal Hukum Lex Generalis, 2025)
Certificates serve as valid proof of ownership under Indonesian law with the primary objective of providing legal certainty’. However, why is it that a land certificate must sometimes be annulled? Such situations may lead to ambiguity in legal implementation and result in a lack of legal certainty and protection for certificate holders. This study raises several legal issues: How is the application of the negative publication system with a positive tendency in land registration able to ensure legal certainty over the status of land certificates issued by the Land Office? How should the legal reasoning of judges in annulling Certificate of Ownership No. 212/Pasar Pangururan through Decision No. 35/G/2020/PTUNMDN be analyzed in relation to the value of justice? What are the legal responsibilities of the Head of the Land Office of Samosir Regency in issuing Certificate of Ownership No. 212/Pasar Pangururan to the aggrieved party?. This study is a normative juridical research employing a descriptive analytical approach. he findings indicate that the implementation of the negative publication system with a positive tendency in land registration has not yet maximally provided legal certainty regarding the status of ownership certificates issued by the Land Office, as such certificates can still be subject to legal challenge